An evaluation of the brand campus concept implemented at Mercedes-Benz South Africa: a case study - Samkange, Tichaona (Rhodes University, Faculty of Commerce, Investec Business School, 2009)
Primarily, this research study was concerned with the evaluation of the brand campus concept implemented at then DaimlerChrysler South Africa in 2002, as a case study. Pretoria-based Mercedes-Benz South Africa (Pty) Ltd. (MBSA) is a subsidiary of global vehicle manufacturer Germany's Daimler-Benz AG (DBAG). They are responsible for assembling, distributing and retailing, certain Mercedes-Benz and Mitsubishi vehicle brands, and spare parts. The landmark 1998 DaimlerChrysler global 'merger of equals' was preceded by the 1995 joint venture between Mercedes-Benz and Mitsubishi Motor Corporation. Consequently, three brands (Mercedes-Benz, Chrysler and Mitsubishi) were retailed and marketed under DaimlerChrysler South Africa (Pty) Ltd. (DCSA), positioned next to each other in the same showroom. This report identifies key challenges stemming from this approach, namely: brand strength dilution, more than 80 multi-franchised dealers and multi-branded showrooms, service capacity problems, old working environment and infrastructure, and perceived intra-brand competition. The research evidence suggests that these problems prompted then DCSA to launch the 2000 Dealer Network Strategy (DNS). In the grand scheme of things, the DNS intervention entailed partitioning the dealer network into five brand centres in five metro regions, and eighteen market centres in the rural areas. The brand campus concept was borne out of DNS and proved to be a masterstroke since, the primary focus was on streamlining the retail facilities for DCSA vehicle sales, service and spare parts for both the passenger and commercial vehicles. This study highlights key pillars of the brand campus concept, namely: profitability, brand focus, customer orientation and diversity. The challenge was to address seven major drivers of the brand campus concept, namely: after-sales vehicle support, vehicle service capacity, lead-times, spare parts availability, sales information propagation, behavior of sales personnel and the overall vehicle dealership appearance. Semi-structured interviews constituted part of the evaluation based on the perspectives of five customers, three dealer principals and two MBSA marketing executives. The research evidence, which also came from MBSA documentation and direct observation, shows that this innovative concept has been remarkably successful.
Keywords: Mercedes-Benz of South Africa; DaimlerChrysler -- South Africa; Consumer satisfaction -- Case studies -- South Africa; roduct management -- Case studies -- South Africa; Brand name products -- Management -- Case studies; Brand name products -- Valuation -- Case studies; Marketing -- Case studies -- South Africa; Brand choices -- Case studies -- South Africa; Customer preferences -- Case studies -- South Africa